TOLKAPPIA MEIPADUGAL IN KANNADASAN'S YESU KAVIYAM - Patrick, G. Joseph; Rose, G. J. Leema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Jesus epic composed by the poet Kannadasan is considered one of the most significant texts in the epic genre of the ancient Tamil language. This book is an epic that is written in a manner that is accessible and comprehensible to individuals of all social strata. The poet has composed a poetic rendition of Jesus' complete life story. This research aims to explore the performance of songs as dance with the support of the meipadugal in Tolkappiyam, the first grammar book of the Tamil language. This research was conducted to assist dancers in enhancing their performance of a certain dance by emphasizing the background and character of the song.